2021
DOI: 10.3390/ijerph18116151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Access Site-Related Complications and Quality of Life in Patients after Invasive Cardiology Procedures According to the Use of Radial, Femoral, or Brachial Approach

Abstract: The radial approach (RA) is the most common in invasive cardiology, but depending on the clinical situation, the femoral approach (FA) and brachial approach (BA) are also used. The BA is associated with the highest odds of complications so it is used mainly if a first-choice approach fails. The aim of the study was to assess clinical outcomes after invasive cardiology procedures stratified by the use of the RA, FA, and BA, with a focus on access site-related complications, quality of life (QoL), and patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
7
1
1
Order By: Relevance
“…The results of the present study showed moderate levels of QoL in the pre-PCI period, and an increase in QoL scores 6 and 12 months post-PCI. The QoL measurement prior to this minimally invasive procedure provides significant insights into the selection of patients and offers a base to clinicians to provide individualized care afterward [ 6 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study showed moderate levels of QoL in the pre-PCI period, and an increase in QoL scores 6 and 12 months post-PCI. The QoL measurement prior to this minimally invasive procedure provides significant insights into the selection of patients and offers a base to clinicians to provide individualized care afterward [ 6 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, QoL is monitoring the performance of clinical care, improving safety and outcomes, thus contributing to treatment cost reduction [ 10 , 11 ]. Furthermore, QoL provides the basis for comparing different treatment options, such as the choice of vascular access site and determining predictors of health benefits [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the need for additional S-IVL may be reduced by an escalation of burr size, when the burr-to-artery ratio exceeds over 0.5/0.6, this leads to an increased rate of complications (i.e., slow flow phenomena, dissection, or perforations) [ 39 , 40 , 41 , 42 ]. In addition, this often implies the need for guiding size escalation or even force switching to the transfemoral approach, which additionally affects the amount of peri-procedural access-side bleeding [ 43 , 44 ]. Until rota-lithotripsy’s introduction to clinical practice, the burr escalation maneuver was considered a basic bailout strategy for primarily undilatable lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors determined in this study indicate that vascular access do not have an impact on serious complications, and thus on clinical outcomes in patients with ACS. However, they do influence overall complications, probably due to the most common, mild complication -puncture-site hematoma, which occurs more often in brachial access [28].…”
Section: Discussionmentioning
confidence: 99%